Lack of atrial branch perfusion during acute ischemia is not associated with new-onset atrial fibrillation during STEMI - Marina M. Demidova; Goran Olivecrona; Anton P.M. Gorgels; David Erlinge; Pyotr G. Platonov (International Journal of Cardiology: Heart & Vasculature)
Background and aim: Atrial fibrillation (AF) often complicates ST-elevation myocardial infarction (STEMI). Atrial ischemia due to non-perfused atrial branches may contribute to its underlying mechanisms. We aimed to assess the association between atrial branches perfusion during STEMI and AF occurrence during and after STEMI. Methods: We performed a single-center retrospective register-based cohort study. Consecutive STEMI patients admitted for percutaneous coronary interventions (PCI) during 2007–2010 were included (n = 1960, age 65 ± 12 years, 71 % male) and followed up for 10 years. Clinical characteristics were retrieved from the Swedish national registries. ECGs recorded before, during or after STEMI were exported from a digital archive. Patients with AF documented prior to STEMI and AF after CABG during hospitalization for STEMI were excluded. The endpoint was the first AF episode either during hospitalization or after discharge. Results: Non-perfused atrial branches were observed in 59 out of 212 proximal RCA occlusions and in 4 out of 93 proximal LCX occlusions. All other culprit vessels (n = 1,655) were presumed to be unrelated to atrial perfusion. The absence of atrial branch perfusion was not associated with new-onset AF either during hospitalization or after discharge (HR = 0.79, 95 % CI 0.35–1.78, p = 0.570). Conclusion: The lack of atrial branch perfusion during STEMI was not associated with new-onset AF either during or after STEMI.